Improving critical thinking skills through a Problem Based Learning (PBL) Approach based on Augmented Reality (AR) at SMAN 1 Seunuddon - Muliana, Muliana; Nufus, Hayatun (International Journal of Trends in Mathematics Education Research, 2024)
This research aims to explore improving students' critical thinking skills through the application of the Problem Based Learning (PBL) learning model assisted by Augmented Reality (AR) technology. The research method used was an experiment with a quasi-experimental design, involving two sample groups, namely the experimental group that applied the AR-assisted PBL model and the control group that followed conventional learning methods. This research sample consisted of 60 high school students who were selected purposively. The instrument used in this research is a critical thinking skills test which has been tested for validity and reliability. The results of the validity test show that all question items are valid with a coefficient above 0.6, while the reliability test shows a Cronbach's Alpha value of 0.87, which indicates high reliability. The results of the question difficulty level test show that the questions used are in the moderate category, and the question discrimination power test shows that there is good variation in differentiating students based on their ability level. The data normality test showed that the two groups (experimental and control) were not normally distributed, so data analysis continued using the Mann-Whitney non-parametric test. The results of this statistical test show a significance value of 0.00, which means there is a significant difference between the experimental group and the control group in improving critical thinking skills. This research concludes that the application of the Problem Based Learning learning model assisted by Augmented Reality (AR) can significantly improve students' critical thinking skills.